PENERAPAN TERAPI PIJAT BAYI DALAM UPAYA PENINGKATAN BERAT BADAN DAN KUALITAS TIDUR BAYI DI PUSKESMAS LURASIK TAHUN 2022 (STUDY KUALITATIF) - FITRIYANINGSIH; MARIA FRANSISKA MEOL (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2022)
Background: The golden age period is very important and needs special attention from parents. During the golden age, the brain grows to its full potential, as does physical growth. In addition, this period also appears in the development of the child's personality and the formation of patterns of behaviour, attitudes and emotional expression. If the various needs of children are ignored during the golden age, it is worried that children will experience less than optimal growth and development (dr. Theresia Santi, 2021). Based on a preliminary study conducted by researchers in January 2022 at the Puskesmas Lurasik that the INC, Newborn and Postpartum visits were carried out by Midwives, the total deliveries at the Puskesmas Lurasik reached 54 visits as well as BBL services. As for postpartum visits, it reached 63 visits, because patients who gave birth at the hospital also made postpartum visits at the Puskesmas. Research Objectives: To define the effectiveness of the application of infant massage therapy to increase infant weight and sleep quality at the Puskesmas Lurasik in 2022. Research Methods: This research is operational research using qualitative research methods.Research Results: The results of this study indicate an increase in the baby's weight and sleep quality.Conclusion: There is an effective implementation of Infant Massage Therapy in Efforts to Increase Baby's Weight and Sleep Quality at Lurasik Health Center which was carried out in By. Mrs. Y.A for about 1 month.